2014
DOI: 10.1007/s00210-013-0953-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of C-type natriuretic peptide-induced cGMP and functional responses by PDE2 and PDE3 in failing myocardium

Abstract: Recently, we showed C-type natriuretic peptide (CNP)-induced negative inotropic (NIR) and positive lusitropic response (LR) in failing rat heart. We wanted to study whether, and if so, how phosphodiesterases (PDEs) regulate CNP-induced cyclic 3',5'-guanosine monophosphate (cGMP) elevation and functional responses. Inotropic and lusitropic responses were measured in left ventricular muscle strips and cyclic nucleotide levels, PDE activity and phospholamban (PLB) and troponin I (TnI) phosphorylation were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…Thus, PDE barriers are not a sufficient explanation for the inability of BNP stimulation to reach the same functional compartment as CNP stimulation, unless PDEs other than the ones tested could be involved. The cGMP increase by both BNP (this study) and CNP (Moltzau et al, 2014) is markedly and mainly regulated by PDE2, in line with earlier studies (Castro et al, 2006). Still, the effect of PDE2 inhibition on the cGMP elevation was significantly higher for CNP than BNP (P , 0.05), despite comparable cGMP elevation with the two NPs alone.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, PDE barriers are not a sufficient explanation for the inability of BNP stimulation to reach the same functional compartment as CNP stimulation, unless PDEs other than the ones tested could be involved. The cGMP increase by both BNP (this study) and CNP (Moltzau et al, 2014) is markedly and mainly regulated by PDE2, in line with earlier studies (Castro et al, 2006). Still, the effect of PDE2 inhibition on the cGMP elevation was significantly higher for CNP than BNP (P , 0.05), despite comparable cGMP elevation with the two NPs alone.…”
Section: Discussionsupporting
confidence: 91%
“…Further, we found that concerted effects of phospholamban (PLB) Ser16 and troponin I (TnI) Ser23/24 phosphorylation most likely represent the main mechanisms explaining the cGMP-protein kinase G (PKG)-mediated NIR and LR to CNP (Moltzau et al, 2013). Whereas PDE2 was the major phosphodiesterase-hydrolyzing cGMP generated by CNP, we also found a role for both PDE2 and PDE3 in the regulation of CNP-induced functional responses (Moltzau et al, 2014). Thus, a major discrepancy between cGMP levels and functional responses was revealed.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The cGMP generated by NPR-B has been reported to increase b 1 -adrenoceptor-mediated positive inotropic responses through inhibition of PDE3 (Moltzau et al, 2013). In HF, it is possible that cGMP may affect cAMP signaling via cross-talk regulation by cGMPregulated subtypes of PDEs (PDE2 or PDE3) (Takimoto, 2012;Moltzau et al, 2014b), which leads to an increase in intracellular cAMP and increased contractility; however, whether and to what extent administration of CNP affects the cGMP-cAMP pathway, improving b-adrenergic stimulation and thereby contributing to the beneficial action of CNP in HF, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we measured the plasma levels of cGMP, but we did not measure the cGMP or cAMP levels in the heart. It is possible that its beneficial actions are attributable to the alteration on b-adrenergic stimulation activated by subtype PDEs that regulated the CNP-activated cGMP/protein kinase G (PKG) pathway (Moltzau et al, 2013(Moltzau et al, , 2014b. Finally, the angiotensin receptor neprilysin inhibitor of LCZ696 has demonstrated greater efficacy than enalapril in a phase 3 trial in HF with reduced ejection fraction (Langenickel and Dole, 2012;Singh and Lang, 2015).…”
Section: Study Limitationsmentioning
confidence: 99%